Concept of association in a modern phytosociology (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
The state of arts in the field of phytosociology in Europe is elucidated with special emphasis to association concept and its use for classification of Ukrainian vegetation.
Keywords: phytosociology, methodology, association, vegetation.